Mechanical thrombectomy versus systemic thrombolysis in MCA stroke: a distance to thrombus-based outcome analysis. (7th September 2015) - Lobsien, Donald; Gawlitza, Matthias; Schaudinn, Alexander; Schob, Stefan; Hobohm, Carsten; Fritzsch, Dominik; Quäschling, Ulf; Hoffmann, Karl-Titus; Friedrich, Benjamin
Abstract : Background: Acute ischemic stroke due to occlusion of the middle cerebral artery (MCA) has a poor outcome. The distance to thrombus (DT) from the carotid T can predict the outcome after intravenous thrombolysis (IVT). With a DT <16 mm, fewer than 50% of patients treated with IVT have a favorable outcome. Objective: To compare stent retriever-based endovascular mechanical thrombectomy (MT) plus additional IVT (IVT–MT) with IVT alone. Materials and methods: Patients with MCA occlusion proved by CT angiography with a DT <16 mm, treated with either IVT alone or with stent retriever-based endovascular IVT–MT, were included in this study. Changes in National Institutes of Health Stroke Scale (NIHSS), the 7-day NIHSS, and the 90-day modified Rankin Scale (mRS) scores were analyzed by treatment modality. Results: Of 621 patients, 87 fulfilled all inclusion criteria. Fifty-nine patients were treated with IVT and 28 with IVT–MT. Although patients treated with IVT–MT had had significantly more severe strokes than those treated with IVT alone (initial NIHSS 16 (7–18) vs 14 (5–22); p=0.032), both the short- and long-term outcomes were significantly better in this patient group (NIHSS improvement on day 7: 10.9±6.3 vs 6.7±6.7; p=0.008/90-day mRS: 2 (0.75–2.5) vs 4 (2–6); p=0.003). Conclusions: In patients with an acute MCA occlusion and a DT <16 mm, IVT–MT leads to a significantly better outcome than in patients treated with IVT alone.